Robust enzymatic-mass spectrometric fingerprinting analysis of the fraction of acetylation of chitosans. (1st March 2020) - Wattjes, Jasper; Niehues, Anna; Moerschbacher, Bruno M.
Graphical abstract: Highlights: Enzymatic-mass spectrometric fingerprinting analysis for chitosan FA determination. Independent of pattern of acetylation and the intermolecular variation in FA . Small sample amounts in the microgram scale are sufficient for analysis. The method is as precise as other standard techniques like NMR and titration techniques. Abstract: We developed a rapid and precise method to determine the fraction of acetylation (FA ) of unknown chitosan samples using a combination of enzymatic sample hydrolysis, isotopic labeling, and HILIC-ESI-MS analysis. Chitosans are β-(1, 4)-linked, partially N -acetylated and linear polyglucosamines representing an interesting group of functional biopolymers with a broad range of applications. For a better understanding of their structure-function relationships, it is key to have sensitive, accurate structural analysis tools available to determine parameters like the degree of polymerization (DP), fraction of acetylation (FA ), or pattern of acetylation (PA ). Here, we describe an improved enzymatic/mass spectrometric method for FA analysis of chitosan polymers. In contrast to the original chitinosanase-based mass spectrometric fingerprinting analysis of FA, the new method is independent of the PA and the intermolecular variation in FA (ĐFA ) of the chitosan sample. This allows accurate analysis of heterogeneously de -N- acetylated samples representing the majority of commercially available chitosans.